Comparative Impact of Aerobic vs Resistance Training on Fatigue, Mobility, and Disability in Cancer Patients - Alarab, Azzam; Hroub, Nabeel; Abu Shameh, Ratib (Physical treatments, 2025)
Purpose: Cancer-related fatigue (CRF) is a complex and multifaceted concept. However, the majority of cancer patients are unaware of the fatigue associated with the disease itself or its treatment.  Objective: This study was designed as a randomized controlled trial (RCT) and focused on clarifying the impact of physical exercise on functional activities and fatigue levels in various types of cancer patients.  Methods: 50 patients were randomly selected and then divided into two groups of cancer patients from Augusta Victoria Hospital: An exercise group and a control group. The exercise group participated in aerobic and strengthening exercises, while the subjects in the control group maintained their usual activities. Both groups were assessed before and after the intervention using the brief fatigue inventory (BFI), functional independence measure (FIM), and timed up and go (TUG) test to measure fatigue, functional independence, and mobility, respectively.  Results: The study found significant improements in the experimental group, with fatigue levels decreasing (BFI score from 67.3 to 50.8, P=0.002), functional independence increasing (FIM score from 72 to 87, P<0.001), and enhanced mobility (TUG time from 22.08 to 15.9 seconds, P<0.001). The control group showed minimal changes, with a slight increase in fatigue (BFI score from 55 to 56, P=0.004) and no significant changes in FIM or TUG scores (FIM P=0.591 and the TUG P=0.426).  Conclusion: Therapeutic exercise is crucial for cancer patients, as it alleviates fatigue, improves functional independence, and enhances mobility, ultimately contributing to overall health and quality of life.